Potencial das leveduras em produtos biológicos para agricultura: de promotores de crescimento vegetal a agentes de controle biológico - Alves, Isaias (Universidade Federal de São Carlos, 2026)
In agriculture, yeasts have been increasingly studied due to their natural presence in soils and their ability to establish ecological relationships with plants. Research indicates that these microorganisms can provide several benefits to their associated plants, including the production of phytohormones, the ability of some species to solubilize minerals, the production of siderophores, and their application in the biological control of phytopathogens, among others. Despite this, the potential use of yeasts in agriculture remains less explored compared with other microbial groups. This review aimed to survey the scientific literature on yeasts, their association with plants, and the potential mechanisms involved in plant growth promotion and biological control, in order to better understand the potential of yeasts as plant growth-promoting agents and their use as bioinputs in agriculture. A systematic literature review was conducted using the PubMed, Scopus, and Web of Science databases, including studies published in English over the last 25 years. After the removal of duplicates, articles were selected through the screening of titles, abstracts, and full texts. Studies investigating yeasts isolated from soil and the rhizosphere or obtained from microbial culture collections were included, evaluating their use in plant growth promotion and/or biological control of phytopathogens. The genera Candida, Cryptococcus, Pichia, and Meyerozyma were the most frequently studied regarding plant growth-promoting potential. The studies demonstrated a direct relationship between higher indole-3-acetic acid (IAA) production by yeasts and increased development of inoculated plants, as well as a strong capacity for mineral solubilization. In addition, the studies highlighted the role of yeasts as effective biological control agents.
Potential of yeasts in biological products for agriculture: from plant growth promoters to biological control agents.
Keywords: Leveduras; Promoção de crescimento vegetal; Controle biológico; Yeasts; Plant growth promotion; Biological control; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; 2. Fome Zero e Agricultura Sustentável